Coping Style in Glioma Patients and Their Caregiver: Evaluation During Disease Trajectory - Guariglia, Lara; Ieraci, Sonia; Villani, Veronica; Tanzilli, Antonio; Benincasa, Dario; Sperati, Francesca; Terrenato, Irene; Pace, Andrea (Frontiers in Neurology, 2021)
Background: Patients with glioma have a poor prognosis and, in a short period of time, have to deal with severe forms of disability, which compromise their psychological distress and quality of life. The caregivers of these patients consequently carry a heavy burden in terms of emotional and patient care. The aim of the study is to evaluate the coping strategies of patients and their caregivers during the course of the disease in order to frame the adaptation process in a rapidly progressing pathology. Methods: A prospective study on 24 dyads of patients affected by malignant glioma and their caregivers was conducted between May 2016 and July 2018. Questionnaires designed to identify the coping style (MINI-MaC Scale), psychological distress (HADS scores) and assess QOL (EQ-5D) were administered at two time points: at first lines of treatment and at disease recurrence. Results: Patients and their caregiver structure adaptive coping strategies after diagnosis and after disease recurrence: a coping style oriented towards a fighting spirit prevails. In a dyadic perspective, the adaptation of a member of the couple varies as a function of the other partner’s coping style. Psychological distress affects the coping style expressed. Conclusions: Our data are in line with previous literature on cancer patients, demonstrating that coping style is not a persistent dimension of personality, but can change depending on the situation. Despite the disease rapid course, patients and their caregivers are able to structure adaptive and functional defenses to manage the disease.